An EGaIn-based flexible piezoresistive shear and normal force sensor with hysteresis analysis in normal force direction. (20th September 2016) - Shi, Xiaomei; Cheng, Ching-Hsiang; Zheng, Yongping; Wai, P K A
Abstract: This paper reports a flexible piezoresistive shear and normal force sensor based on eutectic gallium–indium (EGaIn) with fabrication and testing results, which includes further study on the hysteresis analysis in the normal force direction. By using EGaIn as a gauge material, it can detect force on a flexible and stretchable substrate without breaking the gauge wires. However, the liquid-metal gauge wire needs to be packaged and protected in an elastomeric substrate, which creates hysteresis on the sensed resistance with respect to the change of applied force. This paper shows measurement results in static force and also under different speeds of loading force cycles. The relationship between the applied normal force and hysteresis of signal was observed, mainly owing to larger deformation and slower recovering time of the elastomeric substrate that defines the shape of the liquid-metal gauge wire for resistance measurement.